THEORETICAL PROVISIONS OF TECHNICAL AND TACTICAL TRAINING OF YOUNG BASKETBALL PLAYERS (Physical Culture and Sport: Scientific Perspective, 2024)
he paper deals іmproving and enhancing the technical and tactical training of young athletes, with theoretical provisions of technical and tactical training of young basketball players. The main theoretical, organizational and methodological principles of formation and development of technical and tactical training of young athletes and improvement of pupils' game thinking are revealed. The main organizational and methodical directions (methods of teaching young basketball players separate technical methods of the game; methods of teaching young basketball players technical training in general with the indication of the final goal, setting personal tasks, according to the role and determination of sequence of decision of concrete tasks at each stage of sports training of young sportsmen) are allocated.Teaching of separate elements in basketball is solved on the basis of general principles and regularities of teaching motor actions of sportsmen. An action is a combination of indicative, executive, control and corrective elements, where the first element is an action program, on the basis of which the second element is carried out, accompanying the comparison of the obtained results of the event with the set task of the program and control - assessment of progress towards the goal.Three stages of learning a particular technical element: formation (initial training); development (unlearning); consolidation of the element and its improvement. Three stages of learning a particular technical element: formation (initial training); development (unlearning); consolidation of the element and its improvement.The formation of technical training and the sequence of tasks in basketball has two vectors: the gradual adaptation of young athletes to the technical techniques they learn to the conditions of competitive activity; the second vector is the orderliness of learning technical techniques by young basketball players and its methods. The formation of technical training and the sequence of tasks in basketball has two vectors: the gradual adaptation of young athletes to the technical techniques they learn to the conditions of competitive activity; the second vector is the orderliness of learning technical techniques by young basketball players and its methods.
Keywords: technique; tactics; basketball; young athletes